Study of Power Coefficient and Insertion Phase Shift for Organic Magnetic Slab - Li Gao-sheng; Jia Lei; Ming Yong-jin; Cao Qun-sheng (Leida xuebao, 2012)
In this paper, theories of electromagnetic reflection and transmission as well as transmission line are adopted, a simulation method is designed to calculate power transmission coefficient and insertion phase shift, and also the mathematical formulas are deduced that the electromagnetic parameters of material used in radomes must be satisfied to remove the depolarization phenomenon, a single magnetic slab is used to discuss and verify the formulas. A special A sandwich radome, as a example, is calculated to analysis the effects of the magnetic and dielectric materials on the power transmission coefficient and the insertion phase shift. It is found that the phenomenon of depolarization can be avoided for A sandwich radome structure once when r r ε = μ (the relative complex permittivity of the magnetic material equals its relative complex permeability), and the power of transmission coefficient for magnetic material is better, the insertion phase shift is smoother, and the property of transmission performance is better than those of the electric material. Finally, the commercial software HFSS further verifies the correctness of the conclusions and validity of the method.